2022
DOI: 10.1038/s41598-022-24532-8
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model of UTAUT2 to understand consumers' 5G technology acceptance using SEM-ANN approach

Abstract: It has been a decade since the first extensive study on the internet's adoption and use was conducted. Circumstances have changed in the last decade internet has become an essential need for every human being. Socio-psychological, economic, and personal factors play a significant role in shaping human behaviour. But their role in shaping consumer behaviour toward 5G is still unexplored. In order to determine the impact of socio-psychological elements on 5G technology adoption intention, the study integrated cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 54 publications
1
16
1
Order By: Relevance
“…For the purpose of measuring the reaction, we have used a Likert scale of seven points, with "1 indicating strongly disagreeing and 7 as strongly agreeing." According to the findings of the aforementioned research, the Likert scale with seven points is superior to higher-order alternative scales since it is both more accurate and simpler to use [ 52 , 53 ]. Authors have received approval from the Beijing University of Technology’s Ethics committee to conduct this study.…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of measuring the reaction, we have used a Likert scale of seven points, with "1 indicating strongly disagreeing and 7 as strongly agreeing." According to the findings of the aforementioned research, the Likert scale with seven points is superior to higher-order alternative scales since it is both more accurate and simpler to use [ 52 , 53 ]. Authors have received approval from the Beijing University of Technology’s Ethics committee to conduct this study.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Mustafa et al. (2022), in their study to determine consumers' usage and acceptance levels of 5G technologies, found that hedonic motivation influenced behavioral intention. Aranyossy (2022), in his study on online theater applications, mentioned that hedonic motivation partially or completely substitutes or surpasses the effect of performance expectancy in the context of entertainment technology.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, Sunardi et al (2022) demonstrated that hedonic motivation is a significant predictor of behavioral intention in their study, which focused on augmented reality, and participants agreed that the environment was enjoyable and pleasurable. Similarly, Mustafa et al (2022), in their study to determine consumers' usage and acceptance levels of 5G technologies, found that hedonic motivation influenced behavioral intention. Aranyossy (2022), in his study on online theater applications, mentioned that hedonic Participants' likelihood of using the system increased when they perceived resources as sufficient.…”
Section: Discussion and Con Clus Ionmentioning
confidence: 99%
See 2 more Smart Citations